PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU SECOND DI PAJAK TPO TANJUNG BALAI - Simangunsong, Widyawati Febrihani; Marbun, Patar (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The current trend society tends to be interested in buying second-hand shoes for their needs because the prices are affordable and of good quality. However, consumers are not only looking for cheap prices, but also the suitability between the price and quality of shoes (branded) which are cheaper than new shoes. The purpose of the study was to determine the effect of price and product quality on purchasing decisions for second-hand shoes on the TPO Tax of Tanjung Balai City. The type of quantitative research with an associative design. The population is consumers who shop for second-hand shoes is not known for sure due to limited data. The number of samples refers to the Lemeshow formula of 97 people with a purposive sampling technique. The data comes from primary data and the data collection process uses a Likert-scale questionnaire. The data were analyzed using a statistical model consisting of validity tests, reliability, classical assumptions, multiple linear regression, t-test, F-test and coefficient of determination (R2). The results of the study that partially there is an influence of price and product quality on purchasing decisions with each t-count value (2.854 and 7.716) greater than t-table (1.985) and a significance level (0.005 and 0.000) less than 0.05. The F count value > F table (58.319>3.090) was obtained with a significance level (0.000 <0.05), so the hypothesis is accepted, simultaneously price and product quality have a significant influence on purchasing decisions.